Spagetti Bilek Yaralanmalarındaki Tecrübelerimiz ve Retrospektif Analizi - Altundağ, İlker (My University, 2024)
Giriş: Spagetti bilek yaralanması,12 tendon,2 sinir ve 2 arter olmak üzere 16 farklı yapıyı etkileyebilen geniş volar bilek kesilerini ifade etmekte ve en ciddi el yaralanmaları arasında kabul edilmektedir. Çoğu hekim, erken cerrahi onarım ve el rehabilitasyonu kombinasyonunun en iyi tedavi olduğunda hemfikir olsa da, fonksiyonel sonuçların ve bunları etkileyen faktörlerin neler olduğu hala çok iyi anlaşılamamıştır. Amaç: Kliniğimize 'Spagetti Bilek Yaralanması' ile başvuran hastaların, 13 yıllık kayıtlarının retrospektif incelenmesi ile elde edilen verilerin el fonksiyonuna etkisinin değerlendirilmesi ve literatürle karşılaştırılması amaçlanmıştır. Gereç-Yöntem: 01.01.2010–31.12.2022 tarihleri arasında tarafımızca spagetti bilek yaralanması tanısı konan ve bu nedenle opere edilen hastalar Hastane Bilgi Yönetim Sistemi - Nükleus programından tespit edilmiş, ilgili verileri kaydedilmiştir. Ayrıca hastalar telefonla aranarak kontrol muayenesi için davet edilmiştir. Kontrol muayenesi için gelen hastalardan detaylı anamnez alınmış; hastalara ayrıntılı el muayenesi yapılmış ve DASH-T anketi uygulanmıştır. İstatistiksel analizler, IBM SPSS Statistics 21.0 paket programında yapılmıştır. Sonuç: Spagetti bilek yaralanmaları, el için en yıkıcı yaralanmaların başında gelmektedir. Erken cerrahi onarım, titiz diseksiyon, hasta uyumu ve kooperasyonu ile uygun el rehabilitasyonu ve takip muayenelerine düzenli katılım; hastanın optimal iyileşmesi için gereklidir. Çalışmamız spagetti bilek yaralanmaları için literatüre bir katkı niteliğinde olup, özellikle yaralanma etiyolojisi ve fizik tedavinin kalifikasyonu gibi daha önce üzerine gidilmeyen konular irdelenmiş, sonuçları ortaya konmuştur. Anahtar Kelimeler: Spagetti Bilek Yaralanması, Fleksör Tendon, El Bileği, Kombine

Introduction: Spaghetti wrist injury pertains to profound volar wrist lacerations with the potential to disrupt a complex interplay of anatomical structures. These structures encompass a constellation of 16 distinct elements, comprising 12 tendons, 2 crucial nerves, and 2 vital arteries. The prevailing consensus among medical practitioners underscores the amalgamation of early surgical intervention and meticulous hand rehabilitation as the optimal therapeutic approach. Nevertheless, the nuanced intricacies governing functional outcomes and the multivarious factors modulating them remain a subject of profound scholarly investigation, as comprehensive comprehension of these facets remains elusive. Objective: This study endeavours to undertake a comprehensive retrospective analysis of a 13- year dataset encompassing patients who sought medical attention at our clinic due to 'Spaghetti Wrist Injury.' In addition, this study seeks to evaluate the enduring impact on hand functionality during extended longitudinal follow-up, with the ultimate goal of elucidating their comparative alignment or deviation from established findings within the scholarly literature. Materials and Methods: Patients diagnosed with spaghetti wrist injury between January 1, 2010, and December 31, 2022, who subsequently underwent surgical intervention at our institution, were identified through the Hospital Information Management System - Nucleus program and relevant data has been recorded. Contact information for all patients was extracted utilizing the Nucleus platform, facilitating telephone communication and invitations for follow- up examinations. In addition to the collection of anamnestic data, a comprehensive hand examination was conducted for patients attending the follow-up assessment. Finally, patients completed the Disabilities of the Arm, Shoulder, and Hand-Turkish (DASH-T) questionnaire for a comprehensive assessment of their functional status. Statistical analyzes were performed in the IBM SPSS Statistics 21.0 package program. Conclusion: Spaghetti wrist injuries represent one of the most devastating types of hand injuries. Early surgical intervention, meticulous dissection, patient compliance and cooperation, appropriate hand rehabilitation, and regular follow-up examinations are necessary for optimal recovery of the patient. Our study contributes substantively to the existing literature on spaghetti injuries, particularly by examining previously unexplored areas such as injury aetiology and the qualification of physical therapy and presents comprehensive findings on these subjects. Keywords: Spaghetti Wrist Injury, Flexor Tendon, Wrist, Combined
Our Experience and Retrospective Analysis in Spaghetti Wrist Injuries
Keywords: Plastik ve Rekonstrüktif Cerrahi; Plastic and Reconstructive Surgery